Active Virtual Reality Games Reduce Pain Sensitivity in Young, Healthy Adults - Evans, Eric; Naugle, Keith E.; Ovispo, Alex; Kaleth, Anthony S.; Arnold, Brent; Naugle, Kelly M. (Frontiers in Virtual Reality, 2021)
Separately, both physical activity and virtual reality can attenuate pain sensitivity in healthy adults. What is unknown is whether virtual reality combined with physical activity (active virtual reality) could have a greater hypoalgesic effect compared to non-active virtual reality distraction. Objective: The purpose of this study was to determine whether playing physically active virtual reality games exert a greater hypoalgesic effect than a non-active virtual reality game. Methods: Participants (n=36) played three different active virtual reality games (Beat Saber, Holopoint, and Hot Squat) and one non-active virtual reality game (Relax Walk) for 15 minutes on four different visits. During gameplay, participants wore accelerometers on the thigh, wrist, and waist to measure movement intensity and quantity. Pressure pain thresholds were measured on the forearm and thigh immediately prior to gameplay (pretest) and immediately following each gaming bout (posttest). Results: Analysis of the accelerometer data indicated that Hot Squat elicited greater whole-body and lower body moderate to vigorous physical activity compared to the other games. The ANOVA revealed an overall hypoalgesic effect of the virtual reality games on the forearm, regardless of game type. Results also showed a significant hypoalgesic effect on the thigh following gameplay for Hot Squat, Holopoint, and Relax Walk VR. The magnitude of pain reduction was significantly greater during HS compared to the other games. Conclusions: Virtual reality gameplay exerted a hypoalgesic effect on experimental pressure pain. Additionally, the data provided evidence of a potential enhanced hypoalgesic effect of physically active virtual reality compared to non-active VR on pressure pain sensitivity.